2018
DOI: 10.1016/j.otsr.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the alpha defensin lateral flow device (Synovasure) for periprosthetic infections in microbiologically complex situations: A study of 42 cases in a French referral centre

Abstract: III, prospective study of diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The technique most commonly used today for determination of AD from synovial fluid in PJI is commercially available under the name Synovasure ® PJI test. This qualitative test is based on the method of immunochromatographic lateral flow [11,12,19]. The first studies of this method were highly optimistic, with the results of those examinations showed specificity and sensitivity exceeding 90% [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique most commonly used today for determination of AD from synovial fluid in PJI is commercially available under the name Synovasure ® PJI test. This qualitative test is based on the method of immunochromatographic lateral flow [11,12,19]. The first studies of this method were highly optimistic, with the results of those examinations showed specificity and sensitivity exceeding 90% [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…The false positive results obtained by determining AD level in PJI diagnosis may occur in patients with crystal arthropathies [22], as well as in cases of rheumatoid arthritis and reactive arthritis [3,23]. Another possible cause of elevated AD levels in joint fluid can be a presence of metallosis around the joint replacement [13,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, only up to six studies on the lateral flow test were included. After these studies, the diagnostic accuracy of α-defensin for PJI has been widely assessed with inconsistent results [22, 24, 26, 3943]. Therefore, the purpose of the current meta-analysis was to reassess the diagnostic value of laboratory-based immunoassay and the lateral flow test for the detection of synovial fluid α-defensin against PJI.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-three studies [ 12 , 16 , 21 , 22 , 25 , 27 39 , 41 44 , 47 ] were prospective, and twelve studies [ 14 , 15 , 23 , 24 , 26 , 40 , 45 , 46 , 48 51 ] were retrospective. Thirty-four studies [ 12 , 15 , 16 , 21 51 ] were cohort studies whereas only one study [ 14 ] was a case-control study.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four studies [ 12 , 15 , 16 , 21 51 ] were cohort studies whereas only one study [ 14 ] was a case-control study. Twenty-one studies involving a total of 1928 patients (650 joints with PJI) explored the diagnostic accuracy of alpha-defensin [ 12 , 14 , 15 , 23 27 , 29 , 30 , 33 35 , 37 , 38 , 41 , 45 , 46 , 48 50 ], among which eight studies [ 12 , 27 , 29 , 30 , 34 , 35 , 37 , 48 ] used a lateral flow test to assess alpha-defensin, twelve [ 14 , 15 , 24 26 , 33 , 38 , 41 , 45 , 46 , 49 , 50 ] adopted a laboratory-based alpha-defensin immunoassay, and the testing methods used were not reported in one studies [ 23 ]. The mean ages of included patients ranged from 61.7 to 71.0 years, and the proportion of males ranged from 40.3% to 61.5%.…”
Section: Resultsmentioning
confidence: 99%